2005
DOI: 10.1111/j.1525-139x.2005.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of β2‐Microglobulin and Phosphate during Hemodialysis: Effects of Treatment Frequency and Duration

Abstract: Current understanding of beta2-microglobulin (beta2M) and phosphate (or inorganic phosphorus) kinetics during hemodialysis is reviewed. The postdialysis:predialysis concentration ratio for beta2M is determined by dialyzer clearance for beta2M, treatment time, patient body size (specifically, extracellular fluid volume), and total ultrafiltration volume during the treatment. Evaluation of these treatment parameters can be used to calculate dialyzer clearance for beta2M; however, such calculated values are only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 52 publications
3
45
0
6
Order By: Relevance
“…In the analyses excluding these data, our data may reflect inadequate adjustments for these known risk or beneficial factors. However, serum β 2 -M levels in dialysis patients have not been reported to be associated with the above-noted clinical history or medications [3,7,36]. Although we analysed a cohort of prevalent haemodialysis patients who may have a limitation in elucidating the effect of β 2 -M on survival, we found that, after adjustment for several variables that were significant in univariate Cox proportional hazards analysis, serum β 2 -M levels remained associated significantly with both all-cause and non-cardiovascular mortality in multivariate Cox proportional analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the analyses excluding these data, our data may reflect inadequate adjustments for these known risk or beneficial factors. However, serum β 2 -M levels in dialysis patients have not been reported to be associated with the above-noted clinical history or medications [3,7,36]. Although we analysed a cohort of prevalent haemodialysis patients who may have a limitation in elucidating the effect of β 2 -M on survival, we found that, after adjustment for several variables that were significant in univariate Cox proportional hazards analysis, serum β 2 -M levels remained associated significantly with both all-cause and non-cardiovascular mortality in multivariate Cox proportional analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Интактный паратирео идный гормон и β 2 МГ у пациентов с ОПН обычно не исследуются, поскольку их концентрация отражает со вокупность накопления и экскреции этих веществ. Свои токсические свойства они проявляют при сущест венно более высоких концентрациях, характерных для больных с терминальной почечной недостаточностью, определяя, соответственно, нарушения структуры кос тей скелета, патологическую кальцификацию сосудов и специфическое поражение периферических нервов β 2 амилоидом [8]. В настоящем исследовании эти вещест ва использованы исключительно как маркеры, характе ризующие, в первую очередь, не интоксикацию, а транспортные возможности использованных мембран и технологий.…”
Section: результаты и обсуждениеunclassified
“…2-microglobulin. 15 Several tests on single-pool variable volume or pseudo-one compartment models have been performed for the assessment of intradialytic mass balance of single solutes, e.g. calcium, potassium and phosphorus, that play a crucial role for hydro-electrolyte equilibria.…”
Section: Dialysis Modelingmentioning
confidence: 99%